National Initiatives on Salt Substitutes: Scoping Review - Bingxuan Kong; Shanyue Yang; Jiewei Long; Yuhan Tang; Yang Liu; Zeng Ge; Shuang Rong; Yangfeng Wu; Gangqiang Ding; Yuexin Yang; Ping Yao; Chao Gao (JMIR Publications, 2023)
BackgroundSalt substitutes are edible salts that contain less sodium chloride owing to its partial substitution with other minerals, which serve as an important and effective intervention and public health strategy targeting hypertension and its secondary diseases, despite a small degree of controversy. ObjectiveThis study aimed to identify the current salt substitute initiatives in various nations and intergovernmental organizations (IGOs) worldwide and summarize their types and characteristics. MethodsA scoping review was performed based on Arksey and O'Malley's framework and the latest guidance from the Joanna Briggs Institute. Searches were conducted on Google; government websites on food, health, and other related topics; PubMed; Web of Science; and Google Scholar from January 2022 to May 2022. Initiatives related to salt substitutes that were included in the study focused on the involvement of governments or IGOs through the publication of standards, actions, collaborations, funding, and so on. Data were extracted into Microsoft Excel (version 2019; Microsoft Corp) based on predefined items and analyzed using narrative synthesis and frequency count methods. ResultsA total of 35 initiatives from 11 countries (of which 9 are high-income countries) and 3 IGOs were identified. We classified all salt substitute initiatives into 5 types, namely benefit-risk assessments and cautions; plans and actions; regulations and standards; labels; and food reformulation, cooperation with the food industry, and media. More than half (18/35, 51%) of the salt substitute initiatives were launched within the past 5 years. Except for regulations and standards, salt substitute initiatives are, in general, part of the salt reduction framework. No nation or IGO has yet reported on the monitoring and implications of the use of salt substitutes. ConclusionsDespite the limited number of salt substitute initiatives worldwide at present, a review on the different types and characteristics of such initiatives could be helpful in providing a reference for policy makers and stakeholders. Given the great potential of salt substitutes in improving hypertension and stroke, we call on more nations to pay attention to these substitutes and propose salt substitute initiatives in line with their national conditions.